2000
DOI: 10.1002/1098-2779(2000)6:4<309::aid-mrdd10>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of epilepsy in the multiply handicapped

Abstract: The medical management of epilepsy in the multi‐handicapped patient requires careful evaluation, classification, and pharmacologic treatment. It is estimated that 20–40% of patients with mental retardation and cerebral palsy have epilepsy. This review reports the clinical trial data and personal experience related to the use of newer AEDs in the chronic management of epilepsy syndromes in children and adults, as well as information available on the treatment of seizures in individuals with mental retardation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 160 publications
(172 reference statements)
0
21
0
1
Order By: Relevance
“…There are few outcome data to guide the pharmacotherapy of epilepsy in these patients (6). The scope has now widened, however, with the introduction of a range of new AEDs over the last decade (7).…”
mentioning
confidence: 99%
“…There are few outcome data to guide the pharmacotherapy of epilepsy in these patients (6). The scope has now widened, however, with the introduction of a range of new AEDs over the last decade (7).…”
mentioning
confidence: 99%
“…Thirteen of 34 identified cases were fatalities. 2 Additional reports suggest that it mayt be useful in infantile spasms as well, producing complete resolution in several patients. 11 However, felbamate might be safer in children than adults because there have been no reported cases of aplastic anemia in children < 13 years old.…”
Section: Felbamatementioning
confidence: 99%
“…A Cochrane Review of pharmacological interventions for epilepsy in patients with ID concluded that in general, antiepileptic drugs (AEDs) with proven efficacy in the general epilepsy population will also be effective in patients with ID and will have similar adverse effect profiles [3]. Numerous studies have concluded that the newer AEDs improve seizure control and/or have acceptable safety profiles in patients with epilepsy and ID (newer AEDs as a group [4][5][6], lamotrigine [7][8][9], levetiracetam [10][11][12], topiramate [13][14][15][16], gabapentin [17,18], pregabalin [19,20], vigabatrin [21][22][23], tiagabine [24], felbamate [25,26] and oxcarbazepine [5,27,28]). Furthermore, the newer AEDs may have fewer adverse effects and pharmacokinetic interactions with other drugs [6].…”
Section: Introductionmentioning
confidence: 99%